If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6y + 14 + 4y = 34 Reorder the terms: 14 + -6y + 4y = 34 Combine like terms: -6y + 4y = -2y 14 + -2y = 34 Solving 14 + -2y = 34 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -2y = 34 + -14 Combine like terms: 14 + -14 = 0 0 + -2y = 34 + -14 -2y = 34 + -14 Combine like terms: 34 + -14 = 20 -2y = 20 Divide each side by '-2'. y = -10 Simplifying y = -10
| 38-6x=4(-7x+4) | | 12-70-5x=21 | | 13=a/3+9 | | 3y-5=2y-9+2y | | d/2=28 | | -5(4x-2)=-1(3+6x) | | 2(7+m)=-2 | | 21=-3/2x | | 3/4+m=-12 | | 0.6x+300=y | | 8y+3=25 | | xm+xn=p | | 15-4p=2(p-3)+3 | | 6x-3/5=7 | | 5-4k=-49 | | X-1-2x+3=0 | | b+2=5b+2 | | y-2=(1-3) | | 8x+23=33 | | 2c+4=16 | | y-2=(2-3) | | 6x-x=40 | | 12a^3+10a^2-42a= | | mx+nx=pforx | | 2*x^2-2*x+1/2=0 | | 2+6(6x+8)=194 | | x+5+x=2x | | 18=6+2m | | 5(x-6)+33=10-4x+8x | | 12y^2+24y-48x-18=0 | | 3x+15-2x=6 | | 0=t(t^4-6t^2+9) |